Readiness and early response to COVID-19: achievements, challenges and lessons learnt in Ethiopia. Issue 6 (10th June 2021) - Lanyero, Betty; Edea, Zewdu Assefa; Musa, Emmanuel Onuche; Watare, Shambel Habebe; Mandalia, Mayur Lalji; Livinus, Martin Chibueze; Ebrahim, Faiqa Kassim; Girmay, Abiy; Bategereza, Aggrey Kaijuka; Abayneh, Aschalew; Sambo, Boureima Hama; Abate, Ebba
Abstract : Declaration of the novel coronavirus disease as a Public Health Emergency of International Concern necessitated countries to get ready to respond. Here, we describe key achievements, challenges and lessons learnt during the readiness and early response to COVID-19 in Ethiopia. Readiness activities commenced as early as January 2020 with the activation of a national Public Health Emergency Operations Centre and COVID-19 Incident Management System (IMS) by the Ethiopian Public Health Institute. The COVID-19 IMS conducted rapid risk assessments, developed scenario-based contingency plans, national COVID-19 guidelines and facilitated the enhancement of early warning and monitoring mechanisms. Early activation of a coordination mechanism and strengthening of detection and response capacities contributed to getting the country ready on time and mounting an effective early response. High-level political leadership and commitment led to focused efforts in coordination of response interventions. Health screening, mandatory 14-day quarantine and testing established for all international travellers arriving into the country slowed down the influx of travellers. The International Health Regulations (IHR) capacities in the country served as a good foundation for timely readiness and response. Leveraging on existing IHR capacities in the country built prior to COVID-19 helped slow down the importation and mitigated uncontrolled spread of the disease in the country. Challenges experienced included late operationalisation of a multisectoral coordination platform, shortage of personal protective equipment resulting from global disruption of importation and the huge influx of over 10 000 returnees from different COVID-19-affected countries over a short period of time with resultant constrain on response resources.